2005
DOI: 10.1021/ac051398q
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Enhanced Desorption/Ionization on Silicon Mass Spectrometry

Abstract: Perfluorinated surfactants are demonstrated to dramatically enhance desorption/ionization on fluorinated silicon (DIOS) mass spectrometry. Perfluorooctanesulfonic acid improved the signal-to-noise ratio of tryptic digests and gave a 3-fold increase in the number of peptides identified. Similar results were also obtained using perfluoroundecanoic acid; yet among the seven different surfactants tested, controls such as nonfluorinated sodium dodecyl sulfate or fluorinated molecules with minimal surfactant activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 54 publications
1
37
0
Order By: Relevance
“…The effect was most pronounced for carbamazepine, which is a polycyclic alkaline drug. The detection limit achieved for propranolol desorbed from the surface of oxidized GCB is comparable to that for DIOS chip [27].…”
Section: Enhancement Of Saldi-ms Signal-to-noise Ratiosmentioning
confidence: 84%
“…The effect was most pronounced for carbamazepine, which is a polycyclic alkaline drug. The detection limit achieved for propranolol desorbed from the surface of oxidized GCB is comparable to that for DIOS chip [27].…”
Section: Enhancement Of Saldi-ms Signal-to-noise Ratiosmentioning
confidence: 84%
“…It was found that the addition of ammonium citrate to the biological materials helps to reduce contaminant interferences present in biological solutions. Another study used perflorinated surfactants to clean up tryptic digests prior to DIOS analysis and identification of the peptide fragments (Nordstrom et al, 2006). The use of DIOS to determine enzymatic activity was also further expanded to obtain high throughput screening information (Shen et al, 2004a), including DIOS plates with 96 and 384 spots to accomplish high throughput screening of enzyme activity and inhibition.…”
Section: Protein Analysismentioning
confidence: 99%
“…Although DIOS [17] and silicon-NP-assisted LDI [13] also have higher salt tolerance, the preparation of AuNPs is facile and does not require the use of UV light, electrochemical etching, HF etching, or fluorinated derivatives. Additionally, the detection of carbohydrates by DIOS is successful only in the presence of perfluorinated surfactants, which were spotted on the DIOS chip [30].…”
Section: Carbohydrates Gm1 Indolamines and Angiotensin Imentioning
confidence: 99%